Peritoneal Tuberculosis as a Final Result of Diagnostic Conundrum: A Case Report - Ananda Febriani Aulia1 , Azizman Saad2 , Zarfiardy Aksa Fauzi2 , Ari Hidayat3 , Yenni Oktavia4 , Wiw (Indian Journal of Forensic Medicine & Toxicology, 2021)
Peritoneal tuberculosis is a disease which can mimic malignancy especially in women present with ascites andelevated CA125 levels. It always should be considered in the differential diagnosis. Peritoneal tuberculosiswith ambiguous patient symptoms and diagnostic difficulties still poses a great challenge in clinical practice.A 33 years old woman was admitted to hospital with complaints of abdominal pain and shortness of breath.Initially, elevated serum antigen CA-125, ascites, pleural effusion, and multiple suspicious nodules in thelungs and abdominal cavity on CT were found, thus, diagnosing advance stage ovarian cancer. Biopsylaparotomy was performed, and post-operative histological examination was peritoneal tuberculosis. Thepatient was treated with first-line antituberculosis agents and discharged home. Almost in all other cases,peritoneal tuberculosis is diagnosed only after surgical intervention.